Modified Microstructures and Corrosion Behaviors of Mg-Gd-Cu Alloys through Annealing Treatment. Issue 10 (4th October 2021) - Zhong, Shiyu; Zhang, Dingfei; Chai, Sensen; Xu, Junyao; Zhang, Xuxin; Han, Xing; Liu, Zheng; Sheng, Yunfei; Jiang, Bin; Pan, Fusheng
Abstract : Corrosion rates of ideal Mg alloys used for sealing tools in petroleum industry should be able to be altered to adapt to different downhole environments, and corresponding mechanisms of modified corrosion rates need to be clarified. In this study, annealing treatments were carried out at 400 or 450 °C for 2 h to tune the microstructures and corrosion rates of Mg-2Gd- x Cu ( x = 0, 0.5 and 1 wt.%). Microstructures were characterized by scanning electron microscope, X-ray diffractometer and electron backscatter diffraction while corrosion behaviors were investigated by immersion and electrochemical tests. The results showed that after annealing, the growth in the average second phase size and the average grain size, the weakened basal texture and the eliminated residual stress contributed to reduced corrosion rates. As a result, corrosion rates of Mg-2Gd-0.5Cu and Mg-2Gd-1Cu decreased obviously but were still higher than 30 mm·y −1 after annealing, the recommended minimum corrosion rates. It proved that a gradient of corrosion rates of Mg-Gd-Cu can be achieved through annealing treatment, which were beneficial to further application of Mg-Gd-Cu in the field of oil and gas exploitation.